TECHNOLOGY FOR CREATING THE TOPOLOGY OF PRINTED CIRCUIT BOARDS USING POLYMER 3D MASKS - Igor Nevliudov; Evgeny Razumov-Fryzyuk; Dmytro Nikitin; Danila Bliznyuk; Roman Strelets (Сучасний стан наукових досліджень та технологій в промисловості, 2021)
The subject of research is the influence of factors of exposure of two-dimensional images on the topology of conductors in the manufacture of printed circuit boards by the method of three-dimensional polymer photomasks. The purpose of the work is ensuring the accuracy and preservation of the geometric dimensions of the conductors of printed circuit boards during LCD exposure of masks on the work piece. To achieve this goal, it is necessary to solve the following tasks: to analyze photolithography technology and types of polymer 3D printing; to develop a technological process for exposing photopolymer masks to a printed circuit board blank using 3D printing technologies; to conduct experimental studies to determine the optimal exposure parameters; on the basis of the empirical results obtained, to calculate the correlation coefficients of the factors for recall; to construct a linear regression model of the dependence of the deviations of the geometric dimensions of the printed conductors on the parameters of solutions for etching and exposure conditions. Results: The constructed regression models will become the basis for creating a software database that optimizes the initial images of the topology of printed conductors in the automated production of printed circuit boards. This will simplify the process of developing the topology of printed circuit boards, taking into account the real influence of the parameters of the technological operations of etching and exposure on the thickness of the tracks of the conductors of the printed circuit boards, which will reduce the proportion of rejects in the manufacture of single- and double-sided printed circuit boards. Conclusions: an LCD exposure technology and a method for studying the effects of exposure factors on the quality of printed circuit board topology are proposed, which provide sufficient empirical data to create regression models for calculating the influence of technological factors on the final dimensions of conductive paths in the production of printed circuit boards. Further development of the proposed technology will make it possible to manufacture rigid and flexible printed circuit boards completely, with conductive paths, a dielectric base, electronic elements that can be used in various devices.